Assessment of Ganglion Cell Complex and Peripapillary Retinal Nerve Fiber Layer Changes following Cataract Surgery in Patients with Pseudoexfoliation Glaucoma - Ahmed A. Abdelghany; Moataz A. Sallam; Abdallah A. Ellabban (Journal of Ophthalmology)
Purpose. To assess eye pressure, ganglion cell complex, and retinal nerve fiber layer changes following cataract surgery in patients with pseudoexfoliation glaucoma. Methods. Eighty-five patients with pseudoexfoliation glaucoma (PEXG) were included in the study. They were divided into two groups; the first group included patients with PEXG and cataract who underwent phacoemulsification (pseudophakic group; n = 40 eyes). The second group included patients with PEXG without cataract (control group; n = 45 eyes). Both groups were on antiglaucoma treatment. IOP changes after surgery and the ganglion cell complex (GCC) and peripapillary retinal nerve fiber layer (pRNFL) thicknesses were evaluated in patients underwent cataract extraction surgery compared to controls that did not have cataract, nor underwent surgery. Both groups were followed up postoperatively for 18 months. Results. There was no difference in the mean age and glaucoma stage in both groups (P=0.242 and 0.70, respectively). In the pseudophakic group, the mean IOP significantly dropped from 20.43 ± 0.90 to 17.00 ± 2.75 mmHg at the end of the follow-up period (P≤0.001). Slight decrease (≈3 μm) was recorded in the mean GCC thickness of the pseudophakic patients from the baseline at the end of the follow-up period. This decrease was lower than that of the controls (≈5 μm). No significant pRNFL changes were recorded all over the postoperative visits (88.78 ± 22.55 μm at 3 months, 88.67 ± 23.14 μm at 6 months, 87.62 ± 23.04 μm at 12 months, and 87.32 ± 22.61 μm at 18 months) as compared to preoperative value (90.28 ± 22.31 μm) with P=0.335, 0.387, 0.158, and 0.110, respectively, or controls (89.69 ± 21.76 μm, 88.73 ± 21.08 μm, 87.33 ± 20.67 μm, and 87.23 ± 20.54 μm with P=0.850, 0.990, 0.951, and 0.984). Conclusion. Phacoemulsification and IOL implantation may aid in managing pseudoexfoliation glaucoma by lowering IOP and slowing the rate of GCC and pRNFL losses over a short-term period.